ALMACAL VII: first interferometric number counts at 650 μm. Issue 2 (12th May 2020) - Klitsch, A; Zwaan, M A; Smail, Ian; Péroux, C; Biggs, A D; Chen, Chian-Chou; Ivison, R J; Popping, G; Lagos, C; Béthermin, M; Swinbank, A M; Hamanowicz, A; et al.
ABSTRACT: Measurements of the cosmic far-infrared background (CIB) indicate that emission from many extragalactic phenomena, including star formation and black hole accretion, in the Universe can be obscured by dust. Resolving the CIB to study the population of galaxies in which this activity takes place is a major goal of submillimetre astronomy. Here, we present interferometric 650 μm submillimetre number counts. Using the Band 8 data from the ALMACAL survey, we have analysed 81 ALMA calibrator fields together covering a total area of 5.5 arcmin 2 . The typical central rms in these fields is ∼100 μJy beam −1 with the deepest maps reaching σ = 47 μJy beam −1 at sub-arcsec resolution. Multiwavelength coverage from ALMACAL allows us to exclude contamination from jets associated with the calibrators. However, residual contamination by jets and lensing remain a possibility. Using a signal-to-noise threshold of 4.5σ, we find 21 dusty, star-forming galaxies with 650 μm flux densities of ≥0.7mJy. At the detection limit we resolve ≃100 per cent of the CIB at 650 μm, a significant improvement compared to low-resolution studies at similar wavelength. We have therefore identified all the sources contributing to the EBL at 650 μm and predict that the contribution from objects with flux 0.7 mJy will be small.